PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 163 PEKANBARU - Ana Julita; Lazim N '; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted because study result of IPS is still low in fourth grader SD Negeri 163 Pekanbaru. The KKM was determined at the school were: 73 out of 39 students, who reached KKM is 18 students (46.15%), the total number of students who have not reached KKM 21 people (53,84%) with the average is 59,92. This study aims to improve the study result of IPS in IV class SD Negeri 163 Pekanbaru with the implementation of problem solving learning method. Activity of teachers on the first cycle of the first meeting is about 65% in a good category and the second meeting is 75% in a good category. In the cycle II teacher activities increased from cycle I in cycle II first meeting with percentage of 85% very good category, teacher activities increased from cycle I is about 95% percentage with very good category. Student activity on first cycle of first meeting percentage is 60% in less category, and at second meeting percentage is 70% in good category. In the second cycle of student activities was increased in the first meeting percentage of 85% in very well category, and at the second meeting was 90% percentage with very good category. The result of the research got the average base scor score is 59,92 increase in cycle I equal to 15,32% average class 69,10. In cycle II the average class was also increased by 25.16% with classical mastery 75.00.Keywords: Problem Solving, Study Result of IPS